Mad-crip-neurodivergent alliances beyond identity: Reflections from the Global South - Guzmán Martínez, Grecia; Vargas García, Berenice; Alps, Andrea (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2026)
In this text, we offer a critical analysis of the identities, concepts, and movements of Mad Prive, psychosocial disability, and neurodiversity, based on various experiences and reflections shared among the three authors as members of these movements, specifically situating ourselves in Mexico, but in dialogue with other geographical and cultural contexts. First, we present an overview of the historical origins of each social movement, followed by the development of their main demands and political claims. We then describe some tensions between each movement and how identity politics can offer potential in terms of political action for social justice, as well as problems in expanding this potential. We revisit concepts such as Anahí Gabriela González and Martina Davidson's (2022) ‘wild alliances’ and Bergman and Montgomery's (2022) ‘common notions’, among others, to highlight the need and importance of establishing more-than-identity articulations toward the dignification of lives systematically marked as abnormal.
Keywords: disability; identity; mad pride; neurodiversity; social movement